(untitled) (Scientific journal of the Fergana State University, 2023)
At the beginning of the last century, the devotees of the nation, who appeared on the stage of history under the name of Jadids, dreamed of building a state with a developed economy and science. To do this, it was necessary, first of all, to make the nation literate, to educate young people who have acquired modern knowledge. To this end, they established schools in a new way. The Arabic script, which had been used as the main script for more than a thousand years, was reformed due to difficulties in reading and teaching. When this reform did not give the expected result, efforts began to move to the Latin script, like other Turkic nations. After the beginning of the movement for the transition from the Arabic script to the Latin, Uzbek intellectuals published articles on the selection of letters for the existing sounds, their scientific justification, and organized various council meetings and conferences. Should singarmonistic dialects be based on when composing a new alphabet? Or should one be based on corrupt dialects without singarmonism, which cannot reveal the nature of the Uzbek language? This issue was standing on the agenda, and there were a lot of disputes and controversies on this issue. Such controversies also influenced the movement to create a national alphabet, resulting in the creation of four projects by different organizations, as mentioned above. The article compares the projects of this alphabet given on the basis of three sources, and analyzes similar and different aspects in them, their scientific justification in the obtaining of letters, their achievements and disadvantages.